Caracterização e quantificação das emissões de Metano (CH4) em lagoas do Pantanal - Godinho, João Paulo Mariano (2024)
This thesis provides evidence that methane (CH4) fluxes in lentic ecosystems of the Pantanal are heavily regulated by a combination of environmental, ecological, and climatic factors, with significant spatial and temporal variation. Atypical weather events, particularly droughts and heatwaves observed in 2020, increased CH4 emissions, emphasizing the sensitivity of these ecosystems to climate change. The analysis confirmed the decisive influence of organic matter composition and physicochemical conditions in regulating CH4 fluxes, with the highest methane emissions recorded in the marginal sediments of freshwater lagoons (68.23 CH4 m-2 day-1), indicating the influence of sediment composition and organic matter presence on these emissions. A greenhouse gas monitoring index (IMGEE) was developed to understand spatial and temporal emission variations, highlighting higher indices in freshwater lagoons. CH4 emissions are directly related to total organic carbon (TOC) concentrations in the compartment; in the transitional freshwater lagoon group, where the highest emission (27.78 mg CH4 m-2 day-1) occurred, the highest TOCs concentration was found (8.1 mg m-² mg-¹), and in the saline-alkaline lagoon group, the highest emission (5.59 mg CH4 m-2 day-1) was observed in the aquatic compartment, where the TOCw concentration was highest (586 mg/L). An increase in emissions was observed in 2020, both in freshwater and saline-alkaline lagoons, with respective increases of 834% and 631% compared to 2019. In a broader context, during the intensification of the Pantanal drought in 2020, a drying saline-alkaline lagoon showed a massive increase of 5.423% in CH4 emissions. These results underscore the critical importance of lentic ecosystems in the global carbon cycle and the urgency of biomonitoring and management strategies to mitigate their negative impacts, contributing to conservation policies and sustainable management practices in the face of climate change.